CRM Technology and Building Material Suppliers - Love, Peter; Gharavi, H.; Merchant, V. (EMCIS 2008, 2008)
Customer relationship management (CRM) is a comprehensive business and marketing strategy that integrates technology, process and business activities around the customer. CRM is assumed to lead to bottom line benefits for the organization. Advances in information and communication technologies have provided an effective platform to deliver electronic CRM functions. Despite widespread agreement that CRM can have a direct and indirect impact on customer satisfaction, loyalty, sales and profit, the significance of CRM and its features in influencing customer satisfaction has not been well researched in construction. This paper examines the critical success factors of CRM implementation by using a questionnaire survey to obtain data from 68 building material suppliers. Using a structural model and the evaluation technique of partial least squares the analysis revealed that CRM technological initiatives are successful when adequate top management support and accurate knowledge management capabilities, supported by a suitable information technology structure, measured by technological readiness are in place. Construction organizations who are considering the implementation of CRM strategy can utilize these results to become better acquainted with CRM technological initiatives.